A starting level guide for the reading comprehension skill builders series in learning modules for Filipino youth high school students reading levels 1-6 - Liwag, Adelaida Gonzalez 1940- (1978)
This study is a Starting Level Guide which aimed to help alleviate the paucity of instructional materials. The reading selections can also be used as materials for listening comprehension test. This will assist the reading teacher in the setting of his objectives in reading instruction and aid him in the working out of the reading activities in the reading program.